2021
DOI: 10.1159/000511809
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Rockall and Glasgow-Blatchford Scores in Nonvariceal Upper Gastrointestinal Bleeding

Abstract: <b><i>Introduction:</i></b> Risk stratification in patients with nonvariceal upper gastrointestinal bleeding (NVUGIB) is crucial for proper management. Rockall score (RS; pre-endoscopic and complete) and Glasgow-Blatchford score (GBS) are some of the most used scoring systems. This study aims to analyze these scores’ ability to predict various clinical outcomes and possible cutoff points to identify low- and high-risk patients. Secondarily, this study intents to evaluate the appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…This aspect highlights the need for clinical studies (combined with a health economy analysis) that aim to investigate the performance of prediction scores in a large pooled data set of patients with UGIB, adapted to national/regional circumstances. In accordance with this, Maia et al [16] reported the ability of the GBS and RS to predict various clinical outcomes and possible cutoff points to identify low- and high-risk patients in the setting of referral/metropolitan gastroenterology emergency departments. The authors showed that the RS and the pre-endoscopic RS were effective at predicting mortality, and that the GBS was better at predicting transfusion requirement.…”
mentioning
confidence: 84%
“…This aspect highlights the need for clinical studies (combined with a health economy analysis) that aim to investigate the performance of prediction scores in a large pooled data set of patients with UGIB, adapted to national/regional circumstances. In accordance with this, Maia et al [16] reported the ability of the GBS and RS to predict various clinical outcomes and possible cutoff points to identify low- and high-risk patients in the setting of referral/metropolitan gastroenterology emergency departments. The authors showed that the RS and the pre-endoscopic RS were effective at predicting mortality, and that the GBS was better at predicting transfusion requirement.…”
mentioning
confidence: 84%